FRI0241 Association of gastroesophageal factors and progression of interstitial lung disease in the canadian scleroderma research group (CSRG); a large, multi-center database. (23rd January 2014) - Zhang, X.J.; Bonner, A.; Baron, M.; Hudson, M.; Pope, J.E.
Abstract : Background: Interstitial lung disease (ILD) is a common complication of systemic sclerosis (SSc) and is a leading contributor to mortality in SSc patients. Once lung fibrosis occurs, lung function disease course may become stable or progressively decline. While some demographic and SSc-related factors have been associated with development of ILD, little is known about what contributes to progression. We studied the clinical manifestations of SSc-gastroesophageal (GE) involvement in relation to ILD status to determine associations between GE involvement and ILD progression in SSc. Objectives: To determine if GE reflux and dysphagia are associated with progressive ILD as measured by PFTs over three years. Methods: Canadian Scleroderma Research Group (CSRG), a multi-center database of adult SSc patients, annually evaluates and collects patient information including demographics, skin manifestations, internal organ involvement and function assessment data. Using indicators of GE involvement and annual pulmonary function test results from the CSRG database, comparisons were made between no ILD, stable ILD and progressive ILD groups based on FVC% predicted. Univariate and multivariate analysis were used to determine association between GE factors and ILD development and progression. Results: The study included data of 1043 SSc patients with mean age of 55.7 years and mean disease duration of 10.8 years. Among the variables of interest, physician indicators such as esophageal dysmotility (P=0.009) and post-esophageal dilatation (P=0.041) along with patient indicators such as difficulty swallowing (P=0.016), waking up choking (P=0.026) appeared to significantly increase risk of developing ILD. In comparing progressive vs. stable ILD patients, early satiety (p=0.018) a combination term composed of post-dilatation*choking (p=0.042) increased risk of ILD progression. Conclusions: Indicators of esophageal dysmotility and GERD studied appear to be associated with ILD in SSc, with some factors specifically related to progressive ILD. Further, the strong association of an interaction term of both dysmotility and GERD with progressive ILD illustrates a potential dose-response phenomenon. These results hold important implications for management of ILD in SSc. Disclosure of Interest: X. Zhang Grant/Research support from: Canadian Scleroderma Research Group Summer Studentship, CIHR Net Training Grant, A. Bonner: None Declared, M. Baron: None Declared, M. Hudson: None Declared, J. Pope Grant/Research support from: CIHR, Scleroderma Society of Canada, Scleroderma Society of Ontario